Proceedings of pneumotransport 3 - International Conference on the Pneumatic Transport of Solids in Pipes (3rd : 1976 : Bath); Stephens, Herbert Simon; British Hydromechanics Research Association. Fluid Engineering (Cranfield, Bedford: BHRA Fluid Engineering, 1977)
20